2022
DOI: 10.7759/cureus.26714
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Hyperglycemia: Consequences and Management

Abstract: Hyperglycemia during stress is a common occurrence seen in patients admitted to the hospital. It is defined as a blood glucose level above 180mg/dl in patients without pre-existing diabetes. Stress-induced hyperglycemia (SIH) occurs due to an illness that leads to insulin resistance and decreased insulin secretion. Such a mechanism causes elevated blood glucose and produces a complex state to manage with external insulin. This article compiles various studies to explain the development and consequences of SIH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 90 publications
0
35
0
2
Order By: Relevance
“…Stress hyperglycaemia remains a major health emergency issue in our clinical pratice especially in hospital intensive care unit, affecting hundreds of millions of people worldwide [26]. It is reported that infection such as COVID-19 significantly increased rate of new-onset hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Stress hyperglycaemia remains a major health emergency issue in our clinical pratice especially in hospital intensive care unit, affecting hundreds of millions of people worldwide [26]. It is reported that infection such as COVID-19 significantly increased rate of new-onset hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…The Colubridae's high metabolic rates corroborate the blood glucose index to be significantly dependent on the feeding interval only in the studied snakes of this family 22 . A possible reason is a stress-induced hyperglycemia, once cortisol and catecholamines disturb glucose homeostasis, causing insulin resistance and increased gluconeogenesis 29 .…”
Section: Discussionmentioning
confidence: 99%
“…3 Stress hyperglycaemia remains a major health emergency issue in our clinical practice especially in-hospital ICU, affecting hundreds of millions of people worldwide. 40 It is reported that infection such as COVID-19 significantly increased rate of new-onset hyperglycaemia. Surprisingly, 46% of COVID-19 patients showed hyperglycaemia during hospitalization.…”
Section: Discussionmentioning
confidence: 99%